Community-based participatory design of a decade: the FAITH! Cardiovascular Health and Wellness Program - Brewer, LaPrincess C.; Lalika, Mathias; Kyalwazi, Ashley N.; Albertie, Monica; Bowie, Janice; Burgess, Ashya; Burke, Lora E.; Buta, Brian; Cooper, Lisa A.; Crews, Deidra C.; Doubeni, Chyke A.; Elegbede, Walé; et al. (Frontiers in Public Health, 2025)
The FAITH! (Fostering African-American Improvement in Total Health) Cardiovascular Health and Wellness Program is more than a decade-long community-based participatory research initiative aimed at addressing cardiovascular health disparities among African-Americans in Minnesota. Founded in 2013, the program employs a culturally tailored, community-driven approach by partnering with African-American faith communities to promote cardiovascular health through education, digital health tools, and multilevel interventions targeting the social determinants of health. Grounded in community-based participatory research principles, FAITH! prioritizes equitable academic-community partnerships, co-learning, community capacity building, and shared ownership in all aspects of research and implementation. The program’s exemplary innovations include the NIH-funded FAITH! Trial, a randomized clinical trial, testing a mobile health intervention (the FAITH! App) co-created with the African-American community, and the Techquity by FAITH! study. Techquity by FAITH! evaluates the effectiveness of a culturally relevant, community-informed mHealth intervention supported by a Digital Health Advocate network to improve overall cardiovascular health and digital health literacy. During its evolution, FAITH! has addressed emergent public health crises, including the COVID-19 pandemic, by adapting programming to provide emergency preparedness resources, health education, and vaccine outreach. Key outcomes include sustainable church-based health ministries, increased research participation, and successful translation of research into practice. The program has also contributed to research workforce development by mentoring and training diverse early-career scholars and community leaders in community-based participatory research and cardiovascular health equity research. Lessons learned highlight the transformative impact of community-based participatory research in building trust, facilitating culturally relevant dissemination, and sustaining health equity initiatives. The FAITH! model demonstrates a scalable, community-led strategy for advancing cardiovascular health in underserved populations and provides a blueprint for future initiatives aiming to reduce racial health disparities.